Creative reception of Anton Chekhov’s works and personality in the newest russian drama (Gremina’s Sakhalin wife and Llevanov’s Chekhov trilogy) - Журчева, Ольга; Журчева, Татьяна (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2016)
The article discusses the creative dialogue into which the newest Russian drama and theatre works enter with Anton Chekhov’s dramaturgy and his personality. Yelena Gremina and Vadim Levanov move along different trajectories to interpret the writer and his characters. Still, those various methods of creative reception help both playwrights to understand Chekhov’s philosophy and rethink it in the context of contemporary life and contemporary art.